The Shifts of Conventional Context Element Aspects: Towards a Cyberpragmatics Perspective - R. Kunjana Rahardi (JURNAL ARBITRER, 2020)
This study aims to describe the forms of shifting conventional context elements to a virtual external context in the cyberpragmatics perspective. The data of this study were manifestations of the shifts in the contexts. The substantive data source of this study was various kinds of utterances and the formulation of the context containing realizations of the shifts in the conventional external context. The locative data source was social media that published a variety of utterances and the context in which there was a shift in the context elements that could be collected by the researcher around the time of the study. The data collection method applied was the listening method, focusing on the free engaged and profound method of listening. The technique used in applying the listening method was the note-taking technique. The data were then classified and verified further. The verified data were then triangulated to experts of pragmatics, especially cyberpragmatics. Data analysis was carried out by applying distributional method to cover the linguistic dimension of this study. As for the non-linguistic dimension, the researcher applied the extralingual equivalent method. The results of this study were the manifestations of the context shifts as follow: (1) shifting aspects of context element of speech setting, (2) shifting aspects of context element of objectives of speaking, (3) shifting aspects of context element of speech participants, (4) shifting aspects of context element of speech atmosphere, (5) shifting aspects of context element of speech channel, (6) shifting aspects of context element of speech genre and (7) shifting aspects of context element of verbal acts.